Professional ASP.NET 4.5 in C# and VB - Jason N. Gaylord, Gaylord; Christian Wenz, Wenz; Pranav Rastogi, Rastogi; Todd Miranda, Miranda; Scott Hanselman, Hanselman; Scott Hunter, Hunter (Wiley-Blackwell, 2013)
The all-new approach for experienced ASP.NET professionals! ASP.NET is Microsoft's technology for building dynamically generated web pages from database content. Originally introduced in 2002, ASP.NET has undergone many changes in multiple versions and iterations as developers have gained a decade of experience with this popular technology. With that decade of experience, this edition of the book presents a fresh, new overhauled approach. A new focus on how to build ASP.NET sites and applications relying on field-tested reliable methods Integration of "One ASP.NET" philosophy treating ASP.NET Web Forms and ASP.NET MVC as equal tools each with their proper time and place Coverage of hot new ASP.NET 4.5 additions such as the Web API, Websockets and HTML5 & CSS3 use in layout but only to the extent that the tools themselves are practical and useful for working ASP.NET developers Professional ASP.NET 4.5 in C# and VB is an essential tool for programmers who need to be productive and build reliably performing sites with the latest ASP.NET Framework and Visual Studio.